Redistribution of Outpatient Oncologic Surgical Specialty Referrals During COVID-19. Issue 10 (October 2021) - Sutjiadi, Brian; McRae, Joyce; Silva, Trevor; Selleck, Matthew; Reeves, Mark; Garberoglio, Carlos; Lum, Sharon
Background: Initial reports of significantly worse outcomes for cancer patients with COVID-19 led to guidelines for triaging surgical cancer treatment. We sought to evaluate the effects of the COVID-19 pandemic on oncologic surgical specialty referrals. Methods: We compared referrals to oncologic surgical specialty clinics at an academic tertiary care institution following implementation of stay-at-home orders in California (3/19/20–7/31/20, "COVID") to the same time period the year prior (3/19/19–7/31/19, "Pre-COVID"). The number of appointments, consulted surgical services, insurance types, acuity of diagnoses, and times from referral to first appointment (TRFA) were assessed. Results: The overall number of patients seen in matched time periods decreased by 21.6% from 900 (pre-COVID) to 705 (COVID). Proportions of patients with malignant and suspicious diagnoses, surgical and thoracic oncology visits, and Medicaid insurance differed from comparison groups during the COVID period ( P < .05). Overall median (interquartile range) TRFA decreased from 14 (20) to 12 (19) days ( P = .001) during COVID. Conclusion: After implementation of stay-at-home orders, higher acuity and vulnerable patients were appropriately seen in oncologic surgical specialty clinics. While the long-term effects of decreased clinic visits during COVID remain uncertain, further examination of scheduling practices that led to shorter referral times may identify methods to improve timeliness of care and surgical oncologic outcomes in non-pandemic settings.